Virtual Wellness Program for Employees during Pandemic Covid-19 - Chaturvedi, Shweta; Singh Rathore, Amit (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Virtual employee wellness programs are initiatives designed to encourage healthy habits in remote team members. Implementing employee wellness program create a win-win situation between employer and employees. Employer win with reduce tangible cost in the area of healthcare, disability, absenteeism, and employers will pivot wellness programs to empower them to better cope with the health crisis and reduce their health risks amid the pandemic and beyond. The components of employee wellness programs can vary greatly from company to company, but the expected benefits that are sought remain similar. Wellness programs have the ability to change the way people feel about their work environment and also change the way people perform their work .A good wellness program helps employees achieve their aspirations and goals. It makes employees feel valued and cared, and this makes them achieve milestones at work. These campaigns occur through platforms such as Slack, Zoom, and social media. They target all areas of worker health, including mental, physical, social, and financial aspects.